Tourist promotion through the tic´s in Antonio Ante Canton - Imbabura province - Minda Ramírez, Juan Carlos; Ortíz Cumbal, Dennis Victoria; Palomeque Llerena, Tana Vanessa (Tierra Infinita, 2021)
Today, the use of TIC has changed from a competitive advantage to a necessity. Tourism promotion through TIC contributes to the establishment of useful information making it the most powerful tool in the production and transmission of information. For this reason, the purpose of this research was to strengthen tourism promotion in Canton Antonio Ante through the development of a mobile tourist guide application for the Android operating system. For the elaboration of the research, the descriptive research model was applied with a qualitative approach, which allowed the compilation of information by means of the inventory sheets for the tourist attractions of the MINTUR of the year 2017, the realization of interviews and surveys, as well as the compilation of bibliographic material. On the other hand, the non-experimental research was applied together with the inductive method, which facilitated the process of selection and hierarchical structuring of the selected tourist attractions to be implemented in the application of tourist guide. Finally, based on the results obtained, the tourist guide application called Jatun Go was designed, which has the characteristics of simplicity of navigation, utility and multiple functions, and above all, an impeccable visual attraction which exposes the beauty of the tourist attractions of the canton of Antonio Ante
Keywords: Mobile app; Android operating system; promotion; tour guide